Design and Development of Database and its Effective Implementation - Ch. Mary Pushpa,; K.V.M Udaya Lakshmi,; P. Swapna,; G. Vinutha, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Database layout refers to building a appropriate database schema for precise utility items in keeping with the traits of database gadget, setting up database and corresponding applications, in order that the entire gadget can efficaciously collect, store, technique and control information to fulfill the utilization necessities of diverse users. Database layout refers to building a appropriate database schema for precise utility items in keeping with the traits of database gadget, setting up database and corresponding applications, in order that the entire gadget can efficaciously collect, store, technique and control information to fulfill the utilization necessities of diverse users.
Keywords: Database Gadget; DBMS; Database Management Framework; Entity Relationship Diagram; Response Time; Processing Time